Report on the 1st International Workshop on Validation, Verification and Integrity Issues of Expert and Database Systems - T. Bench-Capon; et al. (Information Research: An International Electronic Journal)
In August 1998 an international workshop on validation, verification and integrity issues of expert and database systems was held in Vienna in conjunction with the Ninth Conference on Database and Expert Systems Applications (DEXA'98). This paper reports on the results of this workshop and summarises the issues identified for future research in this area. Details of the presented papers and some additional information can be found at the workshop WWW site